Innovativeness and Consumer Involvement in the Chinese Market - Hynes, Niki; Lo, S. (Singapore Institute of Management, 2006)
There are many markets where two technologies co-exist and compete and predicting consumer choice in this situation is difficult. Existing theories such as the diffusion of innovation go some way to explaining the initial take up of the new technology but in markets where both technologies are in a mature stage, other measures such as consumer involvement may be better indicators of consumer choice. This study examines the relationship between domain specific innovativeness (DSI) and consumer involvement profiles (CIP) in the camera market. It provides evidence of cross cultural validity of these scales and provides initial evidence to suggest consumer involvement is a better predictor of behaviour than innovativeness in markets where two relatively mature technologies compete side by side.